Synthesis, Spectral and Antimicrobial Studies of Lanthanide (III) Nitrate Complexes with Terdentate ONO Donor Hydrazones - N.B. Mallur*, S.K. Patil, V.M. Naik, D.C. Bilehal and (Journal of Experimental Sciences, 2011)
Few lanthanide (III) nitrate complexes with hydrazones obtained by the condensation of 3-[m/p (hydrazino carbonyl)] phenyl sydnone and hydroxy aryl aldehyde or ketones have been synthesized and characterized by elemental analysis, molar conductance measurements, magnetic moments, Infrared, electronic and 1HNMR spectral studies. The spectral studies show that the hydrazones reacts in enol form and as dibasic terdentate ONO donor nature. From the results the coordination number eight for lanthanide ion in the complexes is proposed. The thermal behaviour, stability ranges, percentage of weight loss, percentage of residue obtained after decomposition of Ln (III) nitrate complexes has been studied. Further more the antimicrobial activity of the ligand and its complexes as inhibiting agents has been screened in vitro against two kinds of pathogenic bacteria Salmonella paratyphi, Bacillus cirroflagellosus and pathogenic fungi Aspergillus niger, Candida albicans.